Pengaruh Digitalisasi Data Sekolah dan Kinerja Guru terhadap Prestasi Belajar Siswa di SD Muhammadiyah 2 Denpasar - Fajrin, Wahyutri Imelda; Jumari, Jumari; Hidayat, Tauhid (Faidatuna, 2022)
Data digitalization in the modernization era will make it easier for teachers and students to learn so that it will have an impact on learning achievement. the purpose of this study was to determine: 1) the effect of digitizing school data with student achievement in SD Muhammadiyah 2 Denpasar, 2) the effect of teacher performance on student achievement in SD Muhammadiyah 2 Denpasar, 3) influence between digitizing data and teacher performance on achievement student learning at SD Muhammadiyah 2 Denpasar. This research uses correlational quantitative methods. The population used in this study was fifth grade students totaling 140 students, and the number of samples totaling 104 students using the proportional stratified random sampling technique. Data collection techniques by observation, questionnaire and documentation. Data analysis technique by testing the hypothesis is a product moment correlation technique and multiple correlation analysis. The results of this study indicate that (1) there is an influence between the digitalization of data with student learning achievement where t arithmetic> t table of 2.195> 1.983 significance level of 5%. (2) there is an influence between teacher performance with student achievement where t arithmetic> t table of 2.195> 1.983 significance level of 5%. (3) there is the effect of digitalized data and teacher performance with student learning achievement where the value of Fcount> Ftable is 5.648> 3.08 with a significance level of 5%. From these results it can be concluded there is an influence between: 1) digitalization of school data on student achievement in SD Muhammadiyah 2 Denpasar, 2) teacher performance on student achievement in SD Muhammadiyah 2 Denpasar, 3) Digitalization of school data and teacher performance together towards achievement student learning at SD Muhammadiyah 2 Denpasar.